2017
DOI: 10.1159/000485138
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach to “Right Hepatic Core”: Deepest Region Surrounded by Major Portal Pedicles and Right Hepatic Vein

Abstract: Background/Aims: The resection of hepatic tumors located in the region surrounded by the right hepatic vein (RHV) and the portal pedicles of the right paramedian/lateral sector (the right hepatic core) remains a challenge for liver surgeons. The aim of this study was to demonstrate the surgical techniques and outcomes of our atypical-parenchyma-sparing hepatectomy (atypical-PSH) approach for the removal of tumors in the right hepatic core. Methods: Perioperative records of 1,179 consecutive patients who had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…4 -6,27-30 On the other hand, studies that focused on single MiHs have reported detailed outcomes. 8,[17][18][19][30][31][32][33][34][35][36][37][38][39] However, those studies involved single centers with a limited number of patients, and they reported feasibility and safety of the procedure, rather than its position in surgical practice. The present analysis was the first to provide a broad perspective on different MiHs.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6,27-30 On the other hand, studies that focused on single MiHs have reported detailed outcomes. 8,[17][18][19][30][31][32][33][34][35][36][37][38][39] However, those studies involved single centers with a limited number of patients, and they reported feasibility and safety of the procedure, rather than its position in surgical practice. The present analysis was the first to provide a broad perspective on different MiHs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surgical field becomes deep and restricted by the surrounding liver parenchyma overlying the hepatic hilum. Tani et al (28) reported resections of deeply located tumors in combination with adjacent segments, such as segment 6, 7, or 8, to preserve the liver parenchyma. This approach is very effective when the tumor does not invade the major hepatic veins or hepatic hilum.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…В настоящее время это требование полностью утратило свое значение [3]. Ряд вопросов, в свою очередь, остаются нерешенными и теперь, один из наиболее сложных -планирование объема оперативного вмешательства при расположении новообразований в проекции крупных магистральных сосудов печени [4]. Риск нарушения кровоснабжения и (или) оттока крови, даже зачастую при небольших размерах образования, толкает хирурга на удаление значительной части паренхимы печени.…”
Section: вве де ниеunclassified